Absence of percolation in graphs based on stationary point processes with degrees bounded by two. Issue 1 (30th March 2022) - Jahnel, Benedikt; Tóbiás, András
Abstract: We consider undirected graphs that arise as deterministic functions of stationary point processes such that each point has degree bounded by two. For a large class of point processes and edge‐drawing rules, we show that the arising graph has no infinite connected component, almost surely. In particular, this extends our previous result for signal‐to‐interference ratio graphs based on stabilizing Cox point processes and verifies the conjecture of Balister and Bollobás that the bidirectional k k ‐nearest neighbor graph of a two‐dimensional homogeneous Poisson point process does not percolate for k = 2 k=2 .